Evaluación de los principales parámetros de calidad en carne equina (Ciencia Veterinaria, 2017)
The objective of this work was to study themain quality parameters of horse meat.Wedetermined surface color, texture, moisturecontent, water activity, pH, drainage, lossesduring cooking and microbiological quality ofsamples of horsemeat for the Longissimusdorsi muscle, 48 hours postmortem.The surfacecolour was quantified based on the coordinatesL*, a*, b* of CIE scale, using a Minoltacolorimeter CR300 Series.The texture wasmeasured with aTA-XT2 texturemeter StableMicro Systems Ltd, using Warner-Bratzlerprobe.The surface colour values were L *=34.05, a *= 18.85 and b = 9.25, only the lightness(L *) was slightly lower than beef, thus indicatingdarker meat.As for texture, equinemuscle showed 15% greater shear strength.The values of moisture content (%), aw, pHand cooking losses were 74.3%, 0.982, 5.37and 28% respectively, and none of the casesshowed significant differences with the control.The exudate (drip) in 24 hours whenstored at 4 º C was 2.37%.This value is withinthe range of those reported by authors forbeef. In relation to microbiological quality, initialcounts were made total mesophilic microorganismsand Enterobacteriaceae fromequine meat surfaces, with values of 76.36CFU/g and 74.6 CFU/g respectively.These resultsare within the range allowed by the CAA,this food can be considered as optimal forconsumption.According to the results we canconclude that horse meat would be a highlyviable for human consumption replaces beef.
Keywords: texture; microbiology quality; surface colour